The gastroprotective effect of the essential oil of Croton cajucara is different in normal rats than in malnourished rats - Paula, A. C. B.; Toma, W.; Gracioso, J. S.; Hiruma-Lima, C. A.; Carneiro, E. M.; Brito, A. R. M. Souza (Cambridge University Press, 2006)
It has been shown previously that malnourished rats are resistant to acute gastric lesions but not to subchronic gastric ulceration. It also has been demonstrated that the essential oil obtained from the bark of Croton cajucara (Sacaca) has antiulcer properties. In the present study, the ability of this essential oil to prevent the formation of gastric ulcers in rats fed a diet with 17 % protein (normoproteic rats) or 6 % protein (malnourished rats) was investigated. At a dose of 100 mg/kg body weight, orally, the essential oil significantly reduced the gastric injury caused by indomethacin (25 % after 2 h and 70 % after 4 h) only in normoproteic rats. In the pylorus ligature model, the essential oil increased the pH and gastric volume, but decreased the total acid concentration in both groups when compared to the respective control group. The essential oil significantly increased prostaglandin E2 production in glandular cells by 50 % compared to the controls in both groups of rats. In addition, the amount of gastric mucus was two-fold higher in malnourished rats than in normoproteic rats. The present results show that the enhanced protective effect of essential oil in malnourished rats involved an increase in prostaglandin E2 production and mucus secretion, which are both factors that protect the gastric mucosa against damage. In agreement with this, malnourished rats always had a lower number of acute gastric ulcers.
Keywords: antiulcerogenic activity; Croton cajucara; cytoprotection; essential oil malnourished rats